Vented Individual Patient (VIP) Hoods for the Control of Infectious Airborne Diseases in Healthcare Facilities. (August 2022) - Patel, J.; McGain, F.; Bhatelia, T.; Wang, S.; Sun, B.; Monty, J.; Pareek, V.
Abstract: By providing a means of separating the airborne emissions of patients from the air breathed by healthcare workers (HCWs), vented individual patient (VIP) hoods, a form of local exhaust ventilation (LEV), offer a new approach to reduce hospital-acquired infection (HAI). Results from recent studies have demonstrated that, for typical patient-emitted aerosols, VIP hoods provide protection at least equivalent to that of an N95 mask. Unlike a mask, hood performance can be easily monitored and HCWs can be alerted to failure by alarms. The appropriate use of these relatively simple devices could both reduce the reliance on personal protective equipment (PPE) for infection control and provide a low-cost and energy-efficient form of protection for hospitals and clinics. Although the development and deployment of VIP hoods has been accelerated by the coronavirus disease 2019 (COVID-19) pandemic, these devices are currently an immature technology. In this review, we describe the state of the art of VIP hoods and identify aspects in need of further development, both in terms of device design and the protocols associated with their use. The broader concept of individual patient hoods has the potential to be expanded beyond ventilation to the provision of clean conditions for individual patients and personalized control over other environmental factors such as temperature and humidity.